Development and assessment of a web-based intervention for educating older people on strategies promoting healthy cognition - Vanoh, Divya; Ishak, Intan Hafizah; Shahar, Suzana; Abdul Manaf, Zahara; Mohamad Ali, Nazlena; Mohd Noah, Shahrul Azman (Clinical interventions in aging, 2018)
The increase in the population of aging people has increased the occurrence of cognitive decline leading to predemented stage of dementia, ie, mild cognitive impairment (MCI). The cognitive tools that are web-based have been proven to be useful in decreasing the risk of MCI. Thus, in the present study, an education tool that is web-based, called WESIHAT 2.0 , had been created to educate elderly people about precautionary strategies against MCI. WESIHAT 2.0 was devised in a senior-friendly style, which includes touch screen, greater font size, larger icons, and employed multimedia components of text, images, and videos. The components employed in WESIHAT 2.0 were a screening tool called TUA-WELLNESS, 10 guides for memory improvement, health diary, and guide for a healthy menu. This application assessed a group of 73 candidates consisting of elderly people, health professionals, caregivers, and information technology (IT) professionals for 1 month. All the elderly people, caregivers, and 75% of IT and health professionals were satisfied with the subject matter of WESIHAT 2.0. About more than half of the elderly people, caregivers, and IT and health professionals had given a consensus on the comprehensive ease of the terminologies, sentences, images, table, and advice related to diet included in the web application. Proposals for improvements of the web portal included suggestions such as using smaller sentences, using greater font size, adding more images, and avoiding the use of unfamiliar terminologies. WESIHAT 2.0 is a suitable tool for educating older people about the lifestyle modification strategies to slower progression to cognitive impairment, with regard to the significance of expert advice.